A 30-year-old male with COVID-19 presenting with seizures and leukoencephalopathy. (November 2020) - Khan, Zohaib; Singh, Sukhdev; Foster, Allison; Mazo, Jahinover; Graciano-Mireles, Gira; Kikkeri, Vinaya
First reported in Wuhan, China, Novel Coronavirus Disease-19 rapidly spread causing an outbreak of viral pneumonia and became a pandemic in early 2020. It was later discovered to be caused by Severe Acute Respiratory Syndrome Coronavirus 2, a novel coronavirus. Although the vast majority of cases have primarily involved the respiratory system, some serious cases have started to emerge with central and peripheral nervous system complications. We present the case of a 30-year-old morbidly obese male who initially presented to the emergency department with seizures, altered mental status, and COVID-19 pneumonia. After a 21-day hospital course including 14 days of intensive care unit management, he was stabilized and discharged to a rehabilitation facility. He returned 1 day later with worsening respiratory distress and was found to have acute pulmonary embolism requiring placement of an inferior vena cava filter. After an additional 6 days in the hospital, he was discharged back to the outpatient facility. He returned for a third time with altered mental status, visual and auditory hallucinations, and confabulation. This report provides critical information in revealing a peculiar neurological sequela of COVID-19 induced leukoencephalopathy and its disease course. We hope to shed light on this sequence of events by providing possible mechanisms to aid clinicians in the identification and management of this complication.